The Influence of Room’s Daylighting on the Contrast of Diffuse Screen Image - Masiokas, S.; Pakėnas, V. (Elektronika ir Elektrotechnika, 2005)
The fast progress in use of digital projectors produces a necessity of making a proper screen image. The article presents the research of the image contrasts on diffuse screen in a daylit room. The recommendations for obtaining a proper contrast of screen image using the said projectors and a different location of diffuse screen in daylit interior are given. The calculations of the screen image contrast depending on daylight illuminance are performed on a base of H. Higbie method in MATLAB environment. The data are obtained for such conditions: 5 cases of daylight luminous emittance (5; 10; 20; 30; 50 klm/m2), 4 cases of projector’s luminous flux (1; 5; 2,0; 3,2; 8,0 klm), 2 cases of the window’s shielding (no shield and the shielding of the first window near the screen) and 2 cases of the screen position (the screen is located on the front wall or near the exterior wall set 30º about). 80 variations of contrast charts are computed. It enables to choose the proper location of the diffuse screen in respect of analysed variables. It is advisable to shield first window near the screen and to locate diffuse screen close the exterior wall set 30º about. These conditions enable to obtain the contrast of diffuse screen image K ≥ 0.8 although there are in use low-priced low-powered up-to-date projectors with luminous flux Φ ≥ 2 klm. Ill. 7, bibl. 6 (in Lithuanian; summaries in Lithuanian, English and Russian).